Development of a highly compact and robust chemical reaction mechanism for the oxidation of tetrahydrofurans under engine relevant conditions. (15th September 2020) - Wu, Shaohua; Tay, Kun Lin; Yu, Wenbin; Lin, Qinjie; Li, Han; Zhao, Feiyang; Yang, Wenming
Highlights: A highly compact and robust tetrahydrofurans chemical kinetic mechanism was developed with 56 species and 183 reactions. Genetic Algorithm was introduced to achieve self-adaptive tuning of Arrhenius pre-exponential factor of reactions. Good performance was highlighted by the optimized mechanism against existing experimental results. Abstract: This work presents a compact and robust chemical reaction mechanism for modeling the combustion of saturated furans including tetrahydrofuran, 2-methyltetrahydrofuran and 2-buthyltetrahydrofuran under engine relevant conditions. A decoupling method is adopted to construct the mechanism. The oxidation reaction for the small species is described by a mature and detailed H2 /CO/C1 sub-mechanism, based on which the skeletal sub-mechanisms for tetrahydrofuran, 2-methyltetrahydrofuran and 2-buthyltetrahydrofuran are incorporated via a compact yet robust C2 -C3 sub-mechanism. The sub-mechanisms for the three tetrahydrofuranic fuel components are selected from the detailed chemical mechanisms in the literature via a series of species rate of production analysis, sensitivity analysis, isomer lumping and reaction lumping. The Arrhenius pre-exponential A factors for these selected reaction pathways are then optimized via a single objective genetic algorithm. The resulting mechanism is rather compact consisting of only 56 species among 183 reactions. The performance of the developed mechanism for predicting the combustion chemistry for the three fuel components has been evaluated against the experimental measurements in the literature. Reasonable agreement between the predicted ignition delay times, speciation profiles and laminar flame speeds with the experimental data is achieved for all the cases considered, indicating the high accuracy and robustness of the developed mechanism.